Impact of Triangle Generation Humanitaire Food Security Program on Food Production in Central and West Darfur, Sudan (University of Khartoum Journal of Agricultural Sciences, 2023)
Triangle generation humanitaire (TGH) is a French main NGOactor in the field of food security and livelihood activities in Central andWest Darfur areas since 2003.Seed fair organization is one of its activitiesto provide seeds of cereal and cash crops for farmers in the targetarea(beneficiary farmers) to enhance increasing food production andconsequently food security .This study was carried out to comparebetween beneficiary and non-beneficiary farmers in the production offood crop cereals (Sorghum and millet) as well as comparing seed post-harvest practices. TGH post-harvest survey was conducted in 2013 where868 beneficiary and 918 non-beneficiary farmers were randomly selectedand interviewed through a comprehensive questionnaire. The results ofthe Chi square analysis for testing the hypotheses revealed the acceptanceof the (null) hypothesis that no significant difference between beneficiaryand non-beneficiary farmers with respect to Sorghum and Milletproduction. This similar production could be attributed to otherproduction constraints encountered in the area. Also no significantdifference existed between beneficiary and non-beneficiary farmers inpost-harvest seed practices of seed storage, seed selling and seedconsumption within the house-hold. The two categories consume or sellseeds in the market to fill the food gap during the off-season, which is thetraditional period of food scarcity. The recommendations of the studywere to address production constraints, apply training in seed selectionand storage and intensify post-harvest research for better food access inthe area
Keywords: NGO,; TGH; Food Security; Food Production; Darfur